PENGARUH BUDAYA ORGANISASI DAN LINGKUNGAN KERJA FISIK YANG MEMPENGARUHI PRODUKTIVITAS KERJA MELALUI KEPUASAN KERJA (STUDI PADA KARYAWAN PT. FRISIAN FLAG INDONESIA) - Anggraeni, Lydia; Bagasworo, Wasi (Journal of Accounting, Management and Islamic Economics, 2025)
This research aims to examine "The Influence of Organizational Culture and Physical Work Environment on Work Productivity Through Job Satisfaction (A Study on PT Frisian Flag Indonesia)." The independent variables in this study are organizational culture and physical work environment, while the dependent variable is work productivity. The intervening variable in this research is job satisfaction. Hypothesis testing in this study uses the PLS (Partial Least Squares) method with SmartPLS 4.0 software. Data collection techniques employed a questionnaire using Google Forms to gather respondent information. The sample for this study consists of employees in the production department under the operations director. The analysis results show that organizational culture has a positive and significant effect on work productivity. Job satisfaction has a positive and significant effect on work productivity. The physical work environment has a significant and positive effect on job satisfaction. The physical work environment also positively and significantly affects work productivity through job satisfaction.